A comparative study of serum calcium, magnesium and LDH as the best predictor for severity of pregnancy induced hypertension in the rural population - Salve, Mehul; Rajgire, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders of pregnancy are one of the commonly encountered problem by obstetrician of which, pregnancy induced hypertension leads the list. A number of dietary deficiencies or excesses have been blamed as the cause for preeclampsia over centuries. Studies have shown relationship between dietary deficiencies and incidence of preeclampsia. The lowering of serum calcium and the increase of intracellular calcium can cause an elevation of blood pressure in preeclamptic mothers. Recent investigations suggest that magnesium deficiency could play an important role in the pathogenesis of preeclampsia, particularly in regulating the tonus of arterioles and veins. The relationship of serum leptin and lactate dehydrogenase levels were increased in preeclampsia. Methods: A comparative study to evaluate the levels of serum calcium and serum magnesium and LDH in pregnancy induced hypertension and normal pregnancy and to correlate the serum levels of calcium and magnesium and LDH with the pregnancy induced hypertension. Results: The serum calcium and magnesium has significantly decreased in cases as compared to controls. Whereas the levels of LDH was significantly increased in cases compared to controls. Serum calcium decreased in severe PIH cases compared to mild PIH cases but statistically not significant. Serum magnesium in mild PIH is less compared to severe PIH cases. The decrease is not statistically significant. The increase in LDH in mild case is less compared to severe PIH case. The increase is stastically significant. Conclusion: Routine biochemical evaluation of serum concentration of calcium and magnesium early in pregnancy may be helpful in identifying at risk patients for preeclampsia. Hypocalcemia and Hypomagnesemia in patients with pregnancy induced hypertension may have a cause and effect relationship with the disorder. Amongst the biochemical markers studied LDH level was seen as the best predictor of severity of pregnancy induced hypertension.